Measuring the willingness‐to‐pay for others' consumption: An application to joint decisions of children. Issue 3 (20th November 2017) - Bruyneel, Sabrina; Cherchye, Laurens; Cosaert, Sam; De Rock, Bram; Dewitte, Siegfried
Abstract : We propose a method to quantify other‐regarding preferences in group decisions. Our method is based on revealed preference theory. It measures willingness‐to‐pay for others' consumption and willingness‐to‐pay for equality in consumption by evaluating consumption externalities in monetary terms. We introduce an altruism parameter and an inequality aversion parameter. Each parameter defines a continuum of models characterized by varying degrees of externalities. We study the empirical performance of our method through a simulation analysis, in which we also investigate the impact of measurement error and increased sample size. Finally, we use our method to analyze decisions made by dyads of children in an experimental setting. We find that children's decisions are particularly characterized by varying levels of altruism. We relate this heterogeneity across children to age, gender, and the degree of friendship in dyads.